Transcriptome Profiling of Light-Regulated Anthocyanin Biosynthesis in the Pericarp of Litchi - Zhang, Hong-Na; Li, Wei-Cai; Wang, Hui-Cong; Shi, Sheng-You; Shu, Bo; Liu, Li-Qin; Wei, Yong-Zan; Xie, Jiang-Hui (Frontiers in Plant Science, 2016)
Light is a key environmental factor that affects anthocyanin biosynthesis. To enhance our understanding of the mechanisms involved in light-regulated anthocyanin biosynthesis in the pericarp of litchi, we performed transcriptomic analyses on the basis of Illumina sequencing. Fruit clusters were bagged with double-layer Kraft paper bags at 42 days after anthesis. The bags were removed after 2 weeks. Under light conditions, anthocyanins accumulated rapidly in the pericarp. RNA sequences were de novo assembled into 75,935 unigenes with an average length of 913 bp. Approximately 74.5% of unigenes (56,601) were annotated against four public protein databases. A total of 16,622 unigenes that significantly differed in terms of abundance were identified. These unigenes are implicated in light signal perception and transduction, flavonoid biosynthesis, carotenoid biosynthesis, plant hormone signal transduction, and photosynthesis. In photoreceptors, the expression levels of UV RESISTANCE LOCUS 8 (UVR8), Phototropin 2 (PHOT2), Phytochrome B (PHYB), and Phytochrome C (PHYC) increased significantly when the fruits were exposed to light. This result indicated that they likely play important roles in anthocyanin biosynthesis regulation. After analyzed digital gene expression (DGE), we found that the light signal transduction elements of COP1 and COP10 might be responsible for anthocyanin biosynthesis regulation. After the bags were removed, nearly all structural and regulatory genes, such as UDP-glucose: flavonoid-3-O-glucosyltransferase (UFGT), MYB, basic helix-loop-helix (bHLH), and WD40, involved in the anthocyanin biosynthetic pathway were upregulated. In addition to MYB-bHLH-WD40 transcription complex, ELONGATED HYPOCOTYL (HY5), NAM/ATAF/CUC (NAC), homeodomain leucine zipper proteins (ATHBs), and FAR-RED ELONGATED HYPOCOTYL (FHY) possibly participate in light-induced responses. On the basis of DGEs and qRT-PCR validation, we observed a light-induced anthocyanin biosynthesis and regulation pattern in litchi pericarp. This study enhanced our understanding of the molecular mechanisms governing light-induced anthocyanin biosynthesis in litchi pericarp.